2017
DOI: 10.1016/j.rgg.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory modeling and measurement of the electrical resistivity of hydrate-bearing sand samples

Abstract: In this paper, we describe a setup for modeling hydrate-bearing rock samples and measuring their electrical resistivity at different pressures and temperatures using an AMNB cylindrical four-electrode probe. Methods for modeling hydrate-bearing rock samples and measuring their resistivity are considered. The setup was used in a series of experiments to measure the resistivity of sand samples containing water, ice or tetrahydrofuran (THF) hydrate. It is shown that when the rock pores contain hydrates and a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Here, the impedance value decreases due to the enhancement of electrical conductivity in the test area. Permyakov et al used the resistance method to measure sand samples containing THF hydrate, water, or ice. They reported that the temperature and the type and phase state of the fluid mainly determined the resistivity of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the impedance value decreases due to the enhancement of electrical conductivity in the test area. Permyakov et al used the resistance method to measure sand samples containing THF hydrate, water, or ice. They reported that the temperature and the type and phase state of the fluid mainly determined the resistivity of samples.…”
Section: Introductionmentioning
confidence: 99%